Evaluating role of GeneXpert Mycobacterium tuberculosis and rifampin in diagnosing pediatric tuberculosis - Ul Islam, Junaid; Lone, Parvez Ahmed (International Journal of Contemporary Pediatrics, 2024)
Background: Tuberculosis (TB), an ancient disease, co-evolved with humans for thousands of years. The earliest known molecular evidence was found in a neolithic settlement in the Eastern Mediterranean. The pulmonary form was associated with "tubercles" as early as 1689. The Mycobacterium tuberculosis complex, including M. bovis, M. microti, and M. africanum, is the principal cause of human TB. Despite newer diagnostic and treatment methods, millions still suffer and die from TB. Methods: Between 2015 and 2017, a study at Dalgate Srinagar's intermediate reference laboratory focused on tuberculin sensitivity tests in children with HIV and non-HIV infections. Samples were collected from sputum/gastric aspirate and BAL samples, and Xpert MTB/RIF tests were performed within two hours. Quality control measures were implemented. Results: The study analyzed 137 patients with TB, collecting 227 samples. GeneXpert was the most common test, with 26 patients showing maximum positivity. LJ culture was the most common, with 24 patients showing maximum positivity. Smear microscopy was the most common, with 22 patients showing maximum positivity. GeneXpert, AFB smear, and LJ culture had 63.9%, 63.2%, and 66.7% sensitivity, specificity, and PPV, respectively. Conclusions: A study of 137 pediatric TB patients found that GeneXpert and LJ cultures had higher positivity rates than smear microscopy and LJ culture. Adding GeneXpert to the pediatric diagnostic algorithm could increase the number of microbiologically detected cases. However, sensitivity remains low, highlighting the need for improved diagnostic tests and algorithmic approaches.